Assessing the reasoning skills of biology students in selected senior high schools in the central region of Ghana - Amoah, Charles Agyei; Eshun, Emmanuel (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of the study was to determine the competency level of senior high school (SHS) biology students in reasoning skills and see whether the type of school a student attends and gender has influence on the proficiency in demonstrating reasoning skills when SHS biology students are engaged in laboratory work. The study adopted the “Basic Skills Assessment” approach. The population for the study was 665 SHS 3 elective biology students offering General Science programme for the 2015/ 2016 academic year in the Cape Coast Metropolis in the Central Region of Ghana. The sample consisted of 114 students from both single sex and co-educational Senior High Schools (SHS) offering elective biology for the West African Secondary School Certificate Examinations (WASSCE). Purposive sampling was used to select the schools which participated in the study. One single-sex girls’ school, one single-sex boys’ school and one co-educational (mixed) school were selected. The findings from the study revealed that school type was found to be significantly related to the performance of students at reasoning skills. However, single-sex boys did not differ significantly from mixed schools. Gender was found not to be significantly related to the performance of the students at reasoning skills. However, greater proportion of males exhibited same levels of reasoning skills than their female counterparts. It was recommended that female biology students must be made to do more laboratory work that involves reasoning to improve their reasoning skills.